Mongolians` environmental ethics: nature worship myths - Sukhbat, Soyolmaa (Studia Philosophiae Et Juris, 2024)
This paper selects and analyses Mongolian myths of nature worship, the basis of Mongolian environmental ethics, using etymology, structuralism, modern religion and culture philosophy. When studying the myth of nature worship, myths are regarded as a means of overcompensating the contradictions between nature and culture, facilitating God and human society, and achieving the dreams of people. In this way, myths about the worship of nature have been classified as myths about plants, land, mountains, animals, water and the sky. Mongolian environmental ethics is the basis of the mythical thinking of natural worship, and modern environmental problems need to take into account the belief and dream system. Монголчуудын хүрээлэн буй орчны ёс суртахууны үндэс: байгаль шүтлэгийн домог Хураангуй: Энэхүү өгүүлэлдээ бид монголчуудын хүрээлэн буй орчны ёс зүйн үндэс болсон байгаль шүтлэгийн домгуудыг нэр томьёоны гарвал зүй, структурализм, шашин соёлын орчин үеийн философийн үүднээс шинжлэн судалсан зарим үр дүнг тоймлов. Ингэхдээ домгийг байгаль, соёлын ялгааг арилгах, бурханлиг болон хүний нийгэм хоорондын зуучлагч, хүний хүсэл мөрөөдлийг биелүүлэх хэрэгсэл гэж үзэв. Хэлэлцүүлгийн хэсэгт байгаль шүтэх домгийг ургамал, газар шороо, уул ус, ан амьтан, тэнгэрийн домог гэж ангилсан юм. Байгаль шүтлэгийн Монголчуудын домог нь орчин үеийн хүрээлэн буй орчны асуудлыг шийдвэрлэхэд анхаарах ёстой итгэл үнэмшил, мөрөөдлийн тогтолцоо юм. Tүлхүүр үгс: хүрээлэн буй орчин, ёс суртахуун, байгаль, шүтлэг, домог